PENGARUH STRATEGI MARKETING COMMUNICATION TERHADAP KEPUASAN PELANGGAN SHOPEE FOOD DI SIDOARJO - Akmal, Ichsanuddin; Setianingrum, Vinda Maya (Universitas Negeri Surabaya, 2024)
Online shopping activities have now become a trend in society. One of the marketplace applications that is currently being used is the Shopee application. Shopee is not only engaged in e-commerce, but also develops business in the food sector or commonly called